2008
DOI: 10.1016/j.jpcs.2008.03.039
|View full text |Cite
|
Sign up to set email alerts
|

Electron–phonon and electron–electron interactions in organic field effect transistors

Abstract: Recent experiments have demonstrated that the performances of organic FETs strongly depend on the dielectric properties of the gate insulator. In particular, it has been shown that the temperature dependence of the mobility evolves from a metallic-like to an insulating behavior upon increasing the dielectric constant of the gate material. This phenomenon can be explained in terms of the formation of small polarons, due to the polar interaction of the charge carriers with the phonons at the organic/dielectric i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 10 publications
1
18
0
Order By: Relevance
“…Similar results were used by Fratini et al to justify the existence of small polarons in the channel of single-crystal rubrene transistors 14,17,31,32 that exhibited room-temperature mobilities as high as 20 cm 2 / V s. Their model 32 was used to interpret the dependence of the mobility on both the temperature and the dielectric constant of the gate. 14…”
Section: Strong Coupling Limit and Small-polaron Hoppingmentioning
confidence: 60%
See 3 more Smart Citations
“…Similar results were used by Fratini et al to justify the existence of small polarons in the channel of single-crystal rubrene transistors 14,17,31,32 that exhibited room-temperature mobilities as high as 20 cm 2 / V s. Their model 32 was used to interpret the dependence of the mobility on both the temperature and the dielectric constant of the gate. 14…”
Section: Strong Coupling Limit and Small-polaron Hoppingmentioning
confidence: 60%
“…17,31,32 We now examine both models in a manner that includes the effects of polarization discussed in the previous sections.…”
Section: Charge Transport In the Ofet Channelmentioning
confidence: 99%
See 2 more Smart Citations
“…4c, Supplementary Fig. 33a) due to additional sources of scattering such as electron-electron interactions 35 . The drastic improvement of mobility indicated that the density of charge traps and grain boundaries was significantly reduced 8 .…”
Section: Resultsmentioning
confidence: 99%